Triple-modality nanotheranostics for nasopharyngeal carcinoma: porphyrin-driven photothermal-chemo-radiosensitization with MRI-guided precision - Li, Xiao-Yu; Yang, Ya-Na; Xie, Yue; Huang, Luo; Long, Yan-Yan; Luo, Qian; Wang, Can; Luo, Yan (Frontiers in Nanotechnology, 2025)
Nasopharyngeal carcinoma (NPC) poses significant therapeutic challenges due to its anatomical complexity, hypoxic/fibrotic microenvironment, and high recurrence rates post-chemoradiotherapy, necessitating multifunctional nanoplatforms that overcome resistance and enable precise image-guided therapy. To address this, we developed a multifunctional nanoplatform based on PVA-Ppa, which can be further functionalized through Gd3+ chelation for magnetic resonance imaging (MRI) and radiosensitization, and physically loaded with doxorubicin (DOX) for chemotherapy. Comprehensive characterization assessed physicochemical properties, DOX loading, photothermal efficiency, MRI contrast, and radiosensitization using CNE-2 cells line and CNE-2 xenograft mice. Results demonstrated uniform spherical nanoparticles (36.40 ± 14.67 nm) with high DOX loading capacity (73%) and sustained release. Photothermal irradiation (690 nm) induced rapid temperature rise (>30 °C, P < 0.01) and ROS-mediated apoptosis. Gd-chelation significantly enhanced radiosensitization (sensitization enhancement ratio = 1.69) and radiation-induced apoptosis (40% vs. 17% control). Triple-combination therapy (PVA-Ppa-Gd-DOX + X-ray + laser) achieved complete tumor regression and significantly prolonged survival in vivo. Nanoparticles exhibited high T1 relaxivity (4.17 mM−1s−1 at 7T vs. 1.76 mM−1s−1 for Gd-DTPA), enabling prolonged tumor visualization and real-time therapeutic monitoring. This integrated PVA-Ppa-Gd nanoplatform presents a promising strategy for NPC theranostics, demonstrating potent efficacy in a preclinical model and showing potential to address the challenges of NPC treatment through MRI-guieded precision with synergistic triple-modality therapy. Its translation potential warrants further validation in more complex, orthotopic models.